Biogenic Amines and Endotoxin Content Associated with the Bacterial Numbers of Ground Meat Sold in Bangkok and Nearby Areas - Stonsaovapak, Siriporn; Wattanasiritham, Ladda; Shuvisitkul, Aree (Agriculture and Natural Resources, 2001)
Ninety samples of ground meat; beef, pork and chicken were collected from fresh market and supermarket in Bangkok and nearby areas. Comparing the sources where the samples were collected, microbial loads appeared to be higher in samples from fresh market than supermarket. Changes of biogenic amines concentrations, putrescine and cadaverine were studied in parallel with the development of the microbial population during the storage of ground pork at 0 and 8°C. Changes in sensory scores were also recorded. Pseudomonads and H2S producing bacteria were found to be the dominant microorganisms. Significant changes in putrescine and cadaverine concentration did not occur until the total viable count and pseudomonads exceeded log10 6 to log10 7 CFU/g. Cadaverine concentration increased more rapidly than that of putrescine. Endotoxins were determined by the Limulus amoebocyte lysate test (LAL). LAL titres increased from 10 to 105 during storage of ground pork and correlated with TVC, pseudomonads and Enterobacteriaceae counts were at both 0 and 8°C.